A lender-based theory of collateral☆ - INDERST, R; MUELLER, H (Journal of Financial Economics, 2007)
We consider an imperfectly competitive loan market in which a local relationship lender has an information advantage vis-à-vis distant transaction lenders. Competitive pressure from the transaction lenders prevents the local lender from extracting the full surplus from projects. As a result, the local lender inefficiently rejects marginally profitable projects. Collateral mitigates the inefficiency by increasing the local lender's payoff from precisely those marginally profitable projects that she inefficiently rejects. The model predicts that, controlling for observable borrower risk, collateralized loans are more likely to default ex post, which is consistent with the empirical evidence. The model also predicts that borrowers for whom local lenders have a relatively smaller information advantage face higher collateral requirements, and that technological innovations that narrow the information advantage of local lenders, such as small business credit scoring, lead to a greater use of collateral in lending relationships.